Rare foreign bodies in oro-facial regions - S Mohanavalli; J Jasline David; A Gnanam (Wolters Kluwer Medknow Publications, 2011)
Accidental entry of foreign bodies into the oro-facial region could be due to trauma, therapeutic interventions or iatrogenic. Various foreign bodies and locations have been reported, for example, wood in the orbit, impression material in the maxillary sinus, tooth fragments in the orbit. All these cases presented with inflammatory reaction and formation of infected granuloma, pus discharging sinus and serious complications like intra-cranial abscesses. Foreign bodies sometimes migrate within the tissues and become symptomatic after a certain period of time. In these cases, it is very difficult to correlate the direct relation between the suspected foreign bodies with the present clinical symptoms. The removal of foreign bodies is often a surgical challenge due to a combination of difficulty in access and close anatomical relationship to vital structures. To prevent complications, foreign bodies should be diagnosed and removed on time.